Slug is increased in vascular remodeling and induces a smooth muscle cell proliferative phenotype - Coll Bonfill, Núria (2016)
Objective : Previous studies have confirmed Slug as a key player in regulating phenotypic changes in several cell models, however, its role in smooth muscle cells (SMC) has never been assessed. The purpose of this study was to evaluate the expression of Slug during the phenotypic switch of SMC in vitro and throughout the development of vascular remodeling. Methods and Results : Slug expression was decreased during both cell-to-cell contact and TGFβ1 induced SMC differentiation. Tumor necrosis factor-α (TNFα), a known inductor of a proliferative/dedifferentiated SMC phenotype, induces the expression of Slug in SMC. Slug knockdown blocked TNFα-induced SMC phenotypic change and significantly reduced both SMC proliferation and migration, while its overexpression blocked the TGFβ1-induced SMC differentiation and induced proliferation and migration. Genome-wide transcriptomic analysis showed that in SMC, Slug knockdown induced changes mainly in genes related to proliferation and migration, indicating that Slug controls these processes in SMC. Notably, Slug expression was significantly up-regulated in lungs of mice using a model of pulmonary hypertension-related vascular remodeling. Highly remodeled human pulmonary arteries also showed an increase of Slug expression compared to less remodeled arteries. Conclusions : Slug emerges as a key transcription factor driving SMC towards a proliferative phenotype. The increased Slug expression observed in vivo in highly remodeled arteries of mice and human suggests a role of Slug in the pathogenesis of pulmonary vascular diseases.